Grafomotricidad como estrategia para el desarrollo de la escritura en niños de educación inicial Institución Educativa Inicial Victoria Barcia Boniffatti, Iquitos 2022 - Reategui Vela, Dommi Valentina (2024)
The central objective of the study was to determine the relationship between graphomotor skills as a strategy and the development of writing in early education children of the Educational Institution. Victoria Barcia Boniffatti from Iquitos 2022. We worked with a sample of 195 students. The study was carried out under a basic quantitative approach with a non-experimental design of correlational scope. The study determined in its result a strong positive relationship (rxy= 0.884) and significant (t= 16.410 and a p-value of 0.000<<α=0.05) between graphomotor skills as a strategy and the development of writing in children who participated in the study. It concluded that there is a strong, direct and positive relationship between graphomotor skills as a strategy and the development of writing, as well as its dimensions of graphic and non-graphic activities, in the children of the educational institution analyzed.